Identification of Endophytic Fungi from Rice Grain and It’s Inhibiting Ability by In Vitro Against Pyricularia oryzae Cav. - NI PUTU LINDA SUNARIASIH; I KETUT SUADA; NI WAYAN SUNITI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Identification of Endophytic Fungi from Rice Grain and It’s Inhibiting Ability by In Vitro Against Pyricularia oryzae Cav. Fungal endophyte is a fungi that lives in the tissues of plants without causing disease symptoms on host plants. During symbiotic, many endophyte could produce antibiotic compounds, those can make endophyte microbes become biological control agents against pests and plant diseases. The aims of this study is to determine the types and the number of endophytic fungi spesies that exist in rice seeds stadia, also growth inhibitory ability against Pyricularia oryzae Cav. in vitro. Based on microscopic identification and DNA analysis were found 14 species of endophytic fungi. Endophytic fungi were able to inhibit the develop of Pyricularia oryzae Cav. amount. The greatest inhibitor was Unidentified-2 isolates of 65.6% followed by fungi Phaeosphaeriopsis musae, Sarocladium oryzae, and Sordariomycetes sp., with inhibition of 63.3%, 61.1%, and 58.9% respectively. Key words: endophytic fungi, inhibition, Pyricularia oryzae, rice, In vitro.